Analysis of Market Reaction To The Stock Split Announcement in Listed Companies - admin, Laras Sasti Pratiwi B42111001 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The purpose of this research was to determine how the market reacts because of the stock split announcement. Market reaction seen from the difference in abnormal return before and after the company did a stock split announcement. The samples were 23 companies that go public on the Stock Exchange in 2010-2014 that did not perform stock splits and other policies except the stock split. The data used is secondary data obtained from BEI corner then performed different tests, using paired sample t-test to find whether there is any differences of abnormal return seven days before or seven days after the announcement of a stock split. The results of paired samples t-test was average abnormal return in the seven days before and seven days after the announcement of stock split indicates there are differences. Based on these results, it can be concluded that there are differences the average abnormal return in the seven days before and seven days after the announcement of a stock split. Suggestions relating to the results of this research that not all the information in the capital market is a good information, so for that investor should be able to choose the information as a consideration investment decision. Keywords : Stock Split, Abnormal Return, Market Reaction